A IMPROVING STUDENTS ' ABILITY TO UNDERSTAND THE STORY OF PROPHET BY USING THE MAKE A MATCH LEARNING MODEL (STUDY AT SIXTH GRADE STUDENTS OF AL FIRDAUS ELEMENTARY SCHOOL SURAKARTA) - Wijaya, Novenna Citrasari Muria (Institut Islam Mamba'ul 'Ulum Surakarta, 2024)
This study was motivated by the low learning outcomes of Islamic Religious Education Class VI SD Al Firdaus Surakarta, especially the material Sirah Nabi. So we need an improvement in teaching and learning activities. This study aims to increase knowledge about the methods or learning strategies that can be used for Islamic Religious Education subjects, to improve the learning of Islamic Religious Education subjects, as well as to improve the learning outcomes of Islamic Religious Education material Sirah Nabi in sixth grade students of SD Al Firdaus Surakarta. Through Class Action Research (PTK) by implementing 2 cycles, will be found the influence and efforts to improve the process and learning outcomes of students. The subjects of the study were students of Class VI of SD Al Firdaus Surakarta as many as 16 students consisting of 6 male students and 10 female students. Methods in data collection that are applied utilize field notes, observations, and tests. Worksheet learners (LKPD) is used for data analysis techniques. Criteria for the success of learning improvement in Islamic Religious Education subjects, if the learning outcomes achieved by students have reached the minimum completeness criteria (KKM) 70. From the results of this study obtained data cycle I as many as 16 students, there are 7 students did not reach the KKM, and from the results of Cycle II as many as 7 students have all reached the KKM. The grade point average in cycle I is 69.3, while the grade point average in Cycle II is 79.4. This means that there is an increase in the learning outcomes of Islamic Religious Education subjects Sirah Nabi material in the sixth grade of SD Al Firdaus Surakarta using the make a match method.